IMPLEMENTATION OF INSTAGRAM MEDIA: INFOGRAPHICS AS A POWERFUL FOR STUDENT EXPRESSION OF ART BASED ON HYDROCARBON MATERIALS - Dede Yayah Rokayah; Deni Ainur Rokhim; Hayuni Retno Widarti; Habiddin Habiddin; Afis Baghiz Safruddin; Ananta Ardyansyah (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
This study aims to determine the effectiveness of the implementation of Instagram media, especially on art-based infographics on Hydrocarbons learning using a mixed-method in the form of quantitative and qualitative data collection on the results of students' scores and responses. The research population is SMA Negeri 3 Sidoarjo students with a sample of 120 students who answer questions about art-based Hydrocarbons on the researcher's Instagram feed infographic. Quantitative data were obtained from tests with optional answers, while qualitative data was obtained from the analysis of descriptive questions. The results showed the learning outcomes of students' Hydrocarbons material using an art-based Instagram feed infographic. The advantages of using this Instagram feed infographic media are that it is flexible, it can be accessed anytime and anywhere, the media is liked and often used by students as the millennial generation and reducesthe use of paper. However, what this media lacks is the infographic which is still simple.